An industrial quality control study on B4 Auto Seat Cover Corporation - Avena, Cherrie May (College of Engineering, 2006)
B4 Auto Seat Cover is an automotive parts manufacturer for car companies such as Mitsubishi, Toyota and Nissan. Facing head-on a newly globalized economy, the company has invested time and resources over the past few years trying to set up its Internal Quality Control unit. Currently, the firm is both reevaluating its QS9000 certified lines as well as exploring the certification of other products they currently produce. A two part study was conducted on B4 to address these issues. On one hand, goods that were already controlled using statistical processes were observed, leading to a verification review on their SPC system. On the other, two product lines were selected as case studies on the general quality control system of the company. These were analyzed using a PFMEA-Stream Diagnosis, leading to recommendations on how to improve the quality system already in place. From the verification review, it was seen that the SPC program was sufficiently implemented save for errors arising from manual charting and a number of out of control points. Also, when charted against the specification limits for the insulator cooking temperature, the process turns out heavily incapable. The problem can be solved though by centering the sufficiently narrow curve inside the specification band. Meanwhile, in the second part of the analysis, a complete PFMEA for the lines being analyzed for quality issues was drawn up and was subsequently fed into a stream diagnosis to distill causes for quality failures. From this, it was deemed that the root causes for the quality system failures boiled down to : Operator Errors, Misaligned Dies, Incorrect Press Positioning, Incorrect Machine Settings and Substandard Materials. Recommendations and a subsequent four month implementation plan were both drawn up to address these issues. It was advised that the firm consider having a Methods Engineering Study focusing on streamlining the workflow, a reassessment of the current inspection procedure for raw materials and the possible implementation of an SPC program on the matting temperature and dimensioning for other troublesome products. Also it was suggested that data gathering be expanded to cover other processes the firm may want to implement quality control monitoring on in the future.